Science, ideology and daily life - Marc Van Montagu (Journal of Innovation & Knowledge (JIK), 2018)
Despite years of scientific effort to develop useful and safe biotech crops, ideologies have prevailed and genetically modified (GM-)crops have still not been fully accepted by today's society. This leads one to reflect on the role of Science in society, on what makes scientists credible, and how scientists themselves understand the world we live in. While Science remains a black box for many of the uninitiated, scientists themselves are also generally less-interested in sociology or the economy, such that the coevolution of science and daily life is often frustrated by incomprehension or even disinterest on both sides.
Keywords: O13; Q01; Q16; Q18; 650; Genetically modified organisms (GMOs); Precision agriculture; Genetic engineering